Social Media Technology Tools in Teaching and Learning in UNIMAP: A Study - Ismail, Adila; Bullah Affandy, Habee; Azila Azahari, Nur; Armin Abdul Rahim, Edzham (International Journal of Engineering and Technology, 2018)
This paper illustrates the findings of the study on use of social media technology tools in improving the effectiveness of teaching and learning in Universiti Malaysia Perlis (UniMAP), Malaysia. This study has been conducted in UniMAP, with 500 students from various study backgrounds as respondents. This study uses a quantitative method, with a set of questionnaire is used in data collection. With that, the end result of the research will include the use of the technology in the students’ day-to-day activities. Lastly, a conclusion is made on how the use of social media technology is effective and beneficial to daily teaching and learning activities. Recommendations for improvement are also included.